Porphyry and epithermal alteration-mineralization features along drill hole tadd-159 in the cerro silla norte sector, taguas project, San Juan - Montoya, Andrea (2024)
Fil: Montoya, Andrea. INGEOSUR, Universidad Nacional del Sur. Argentina.